Stereological analysis of elastic fibers of the corpus cavernosum of rats during the aging process - Hota,Thiago (2019)
Abstract Purpose To evaluate changes in the quantity of elastic fibers in the corpora cavernosa of rats during the natural aging process, and to assess the degree of this change by determining volumetric density (Vv) at different ages via stereological analysis. Methods Forty-eight rats, raised under similar conditions, were subjected to the natural aging process and divided into four groups (G1 to G4), according to age at the time of penectomy (6, 9, 12, and 24 months, respectively). Histological sections of the middle segment of the penis were stained with Weigert’s resorcin-fuchsin, and the volumetric density (Vv) of elastic fibers of the corpora cavernosa were determined via stereological analysis. Results There were no statistically significant differences in Vv among groups G1, G2, and G3. These three groups were therefore considered as a single group. The mean Vv of this group showed a statistically significant reduction compared to that of G4 (0.16 vs. 0.11, p<0.05). Conclusion Natural aging in rats was responsible for a reduction in volumetric density of elastic fibers of the corpora cavernosa (approximately 30% decrease in Vv) during senescence.